Former Buruli Ulcer Patients' Experiences and Wishes May Serve as a Guide to Further Improve Buruli Ulcer Management. - Anita Velink; Rebecca J Woolley; Richard O Phillips; Kabiru M Abass; Tjip S van der Werf; Emmanuel Agumah; Janine de Zeeuw; Sandor Klis; Ymkje Stienstra (PLoS Neglected Tropical Diseases, 2016)
BACKGROUND:Buruli ulcer (BU), caused by Mycobacterium ulcerans, is a neglected tropical disease frequently leading to permanent disabilities. The ulcers are treated with rifampicin and streptomycin, wound care and, if necessary surgical intervention. Professionals have exclusively shaped the research agenda concerning management and control, while patients' perspective on priorities and preferences have not explicitly been explored or addressed. METHODOLOGY/PRINCIPAL FINDINGS:To get insight into patient perception of the management and control of Buruli ulcer a mixed methods research design was applied with a questionnaire and focus group discussions among former BU patients. Data collection was obtained in collaboration with a local team of native speakers in Ghana. A questionnaire was completed by 60 former patients and four focus group discussions were conducted with eight participants per group. Former patients positively evaluated both the effectiveness of the treatment and the financial contribution received for the travel costs to the hospitals. Pain experienced during treatment procedures, in particular wound care and the streptomycin injections, and the side-effects of the treatment were negatively evaluated. Former patients considered the development of preventive measures and knowledge on the transmission as priorities. Additionally, former patients asked for improved accessibility of health services, counselling and economic support. CONCLUSIONS:These findings can be used to improve clinical management and to guide the international research agenda.